Poisoning due to the use of electronic cigarette (e-cigarette) - Göney, Gülşen (Journal of Dependence, 2018)
E-cigarettes, also called electronic nicotine delivery systems, personal vaporizers, vape pens, e-cigars, ehookahs or vaping devices, have become increasingly popular in recent years. E-cigarettes are battery-operated devices designed to vaporize a liquid solution of propylene glycol and/or vegetable glycerin in which nicotine or other aromas may be dissolved. According to the International Agency for Research on Cancer (IARC) have shown that e-cigarette contains Group 1 carcinogens such as benzene, ethanol, formaldehyde, iron, alluminium, cadmium, tobacco-specific nitrosamines, polycyclic aromatic hydrocarbons (PAH), and formaldehyde, which can be harmful to humans. Because of the fruit and chocolate flavors inside has increased the number of young people purchasing e-cigarettes. The concentration ratio of nicotine in the liquid content of e-cigarette varies between 6 and 36 mg/mL. The oral LD50 value (lethal dose 50%) of nicotine is 1.0 mg/kg for adult humans. Between 2010 and 2014, the number of calls made to the poison center due to e-cigarette exposure was increased. In a present study provided that case studies and calls were made to the poison centersdue to e-cigarette exposure.
Keywords: Electronic nicotine delivery systems; electronic cigarette; e-cigarette; nicotine; poisoning